Forest Ecosystems and Environments
DOI: 10.1007/4-431-29361-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to elevated CO2 concentration at different scales: leaf, whole plant, canopy, and population

Abstract: Elevated CO 2 enhances photosynthesis and growth of plants, but the enhancement is strongly influenced by the availability of nitrogen. In this article, we summarise our studies on plant responses to elevated CO 2 . The photosynthetic capacity of leaves depends not only on leaf nitrogen content but also on nitrogen partitioning within a leaf. In Polygonum cuspidatum, nitrogen partitioning among the photosynthetic components was not influenced by elevated CO 2 but changed between seasons. Since the alteration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 83 publications
3
15
0
Order By: Relevance
“…Thus, we suggest that photosynthetic acclimation implies a reallocation of N from the photosynthetic machinery to other parts of the plant at elevated CO 2 . Many previous studies have also reported that A in the leaves is determined by the amount of leaf N and its partitioning between the photosynthetic and non-photosynthetic proteins, and among the various photosynthetic components (Woodward, 2002;Hikosaka, 2004;Hikosaka et al, 2005). Our results showed that elevated CO 2 reduced the initial activity of leaf Rubisco by 37.0% at the low planting density, and by 33.1% at the high planting density.…”
supporting
confidence: 65%
“…Thus, we suggest that photosynthetic acclimation implies a reallocation of N from the photosynthetic machinery to other parts of the plant at elevated CO 2 . Many previous studies have also reported that A in the leaves is determined by the amount of leaf N and its partitioning between the photosynthetic and non-photosynthetic proteins, and among the various photosynthetic components (Woodward, 2002;Hikosaka, 2004;Hikosaka et al, 2005). Our results showed that elevated CO 2 reduced the initial activity of leaf Rubisco by 37.0% at the low planting density, and by 33.1% at the high planting density.…”
supporting
confidence: 65%
“…The problem is exacerbated in the middle of the day when plants experience their maximum rate of photosynthesis and high demand for CO 2 . Sufficient CO 2 concentrations are crucial to sustain vegetable production (Hikosaka et al, 2005;Fierro et al, 1994;Buddendorf-Joosten and Woltering, 1994). In the present study, large quantities of CO 2 were generated through microbial fermentation in greenhouses containing CRAM units.…”
Section: Advantages Of Cram Procedures For Co 2 Supplymentioning
confidence: 98%
“…Competition with neighboring plants is one of the most important biotic factors limiting plant growth. Plants in a stand compete with each other for resources, and competition alters morphological and physiological traits of plants (Hikosaka et al 1999(Hikosaka et al , 2005Nagashima et al 2003). These alterations, in turn, result in changes in the microclimate and resource acquisition in the stand, and consequently influence the growth and development of individuals (Hikosaka et al 1999;Nagashima et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed how warming over 6 years influenced growth, biomass allocation, needle chlorophyll concentrations, and carbohydrate status of individuals in a stand. Since light competition is critical for the survival and growth of individuals in dense stands and forest understory (Hikosaka et al , 2005Wang et al 2006), we postulated the following two hypotheses: (1) warming benefits individuals in the stand and causes changes in biomass allocation patterns, and (2) warming causes adjustments in morphology and physiology that allow improved capture of light to support seedling growth.…”
Section: Introductionmentioning
confidence: 99%